Chemical Insights Into the Synthetic Chemistry of Quinazolines: Recent Advances - Faisal, Muhammad; Saeed, Aamer (Frontiers in Chemistry, 2021)
In medicinal chemistry, one of the most significant heterocyclic compounds are quinazolines, possessing broad range of biological properties such as anti-bacterial, anti-fungal, anti-HIV, anti-cancer, anti-inflammatory and analgesic potencies. Owing to its numerous potential applications, in the past two decades, there is an increase in the importance of designing novel quinazolines, exploring promising routes to synthesize quinazolines, investigating different properties of quinazolines, and seeking for potential applications of quinazolines. The present review article describes synthesis of quinazolines via eco-friendly, mild, atom-efficient, multi-component synthetic strategies reported in the literature. The discussion is divided into different parts as per the key methods involved in the formation of quinazoline skeletons, aiming to provide readers an effective methodology to a better understanding. Consideration has been taken to cover the most recent references. Expectedly, the review will be advantageous in future research for synthesizing quinazolines and developing more promising synthetic approaches.